Will Fans Blend: Issues of Access and Participatory Culture within Online Visual Effects Tutorials - Pinsent, Benjamin (Kinephanos)

(untitled) (Université de Montréal Département d'histoire de l'art et d'études cinématographiques, 2025)
This article looks at how special effects fans access the learning materials and develop the skills to recreate the objects of their obsessions. Utilising an autoethnographic approach and taking the 3D modelling software Blender and special effects teacher Andrew Price (aka The Blender Guru) as case studies, the article explores how the platform YouTube affects both Price’s standing within the continuum of fan and professional, and how this affects the mode of address Price uses to teach his viewers, blurring the line between teacher and student.